University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 7 - Section 7.1 - The Logarithm Defined as an Integral - Exercises - Page 401: 22


$-e^{\csc(\pi+t)} +c$

Work Step by Step

Solve $\int e^{\csc(\pi+t)} \csc(\pi+t) \cot(\pi+t)dt$ Let us $p=\csc(\pi+t)$ and $dp=-\csc(\pi+t) \cot(\pi+t)dt$ This implies $\int e^{\csc(\pi+t)} \csc(\pi+t) \cot(\pi+t)dt=-\int e^p dp$ $=- e^p +c$ $=-e^{\csc(\pi+t)} +c$ Hence,$\int e^{\csc(\pi+t)} \csc(\pi+t) \cot(\pi+t)dt=-e^{\csc(\pi+t)} +c$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.